Fibrosis progression in human immunodeficiency virus/hepatitis C virus coinfected adults: Prospective analysis of 435 liver biopsy pairs - Konerman, Monica A. (2014)
Human immunodeficiency virus (HIV)/hepatitis C virus (HCV) coinfection is associated with progressive liver disease. However, the rate of progression is variable and the ability to differentiate patients with stable versus progressive HCV disease is limited. The objective of this study was to assess the incidence of and risk factors for fibrosis progression in a prospective cohort of coinfected patients. Overall, 435 liver biopsy pairs from 282 non-cirrhotic patients were analyzed. Biopsies were scored according to the METAVIR system by a single pathologist blind to biopsy sequence. Fibrosis progression was defined as an increase of at least one METAVIR fibrosis stage between paired biopsies. The majority of patients were African American (84.8%), male (67.7%) and infected with HCV genotype 1 (93.4%). On initial biopsy, no or minimal fibrosis was identified in 243 patients (86%). The median interval between biopsies was 2.5 years. Fibrosis progression was observed in 97 of 282 (34%) patients and 149 of 435 (34%) biopsy pairs. After adjustment, greater body mass index (adjusted odds ratio [aOR]: 1.04 per 1 unit increase), diabetes (aOR: 1.56) and hepatic steatosis (aOR: 1.78) at time of initial biopsy were associated with subsequent fibrosis progression. Between biopsies, elevated serum aspartate and alanine aminotransferase (AST, ALT) (aOR AST: 3.34, ALT: 2.18 for >25% values >100 U/l vs. < 25% values >100 U/l) were strongly associated with fibrosis progression. CONCLUSION: Fibrosis progression is common among HIV/HCV coinfected patients; these data suggest that progression can be rapid. Persistent elevations in serum transaminase levels may serve as important non-invasive markers to identify subsets of patients who are more likely to progress and thus warrant closer monitoring and consideration of HCV treatment.